2017
DOI: 10.1021/acs.joc.7b00030
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Ferrocenyl Phosphates Bearing (Hetero-)Aromatics and [3]Ferrocenophanes toward Anionic Phospho-Fries Rearrangements

Abstract: The temperature-dependent behavior within anionic phospho-Fries rearrangements (apFr) of P(O)(OFc)(EAr) (Fc = Fe(η-CH)(η-CH); E = O; Ar = phenyl, naphthyls, (R)-BINOL, [3]ferrocenophanyl; E = N, 1H-pyrrolyl, 1H-indolyl, 9H-carbazolyl; n = 1-3) is reported. While Fc undergoes one, the Ph-based apFr depends on temperature. First, the aryls are lithiated and rearranged, followed by Fc and N-heterocycles. Addition of MeSO thus gave methylated Fc, contrary to non-organometallic aromatics giving mixtures of HO and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 145 publications
(199 reference statements)
0
49
0
Order By: Relevance
“…Recently electron‐poor pyrrolyl‐, indolyl‐ and carbazolyl‐containing phosphoramidates were converted into stable ferrocenylphosphoramidates . Thus, the CR 2 – O motif was replaced by a CR= N ‐bonded ferrocenyl unit.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently electron‐poor pyrrolyl‐, indolyl‐ and carbazolyl‐containing phosphoramidates were converted into stable ferrocenylphosphoramidates . Thus, the CR 2 – O motif was replaced by a CR= N ‐bonded ferrocenyl unit.…”
Section: Resultsmentioning
confidence: 99%
“…Recently electron-poor pyrrolyl-, indolyl-and carbazolyl-containing phosphoramidates were converted into stable ferrocenylphosphoramidates. [34] Thus, the CR 2 -O motif was replaced by a CR=N-bonded ferrocenyl unit. This imino phosphate motif (type G molecule, Scheme 1) has rarely been described, especially in ferrocene chemistry, where a sole C=N-P(O)Ph 2 unit has been reported, however, without its synthetic procedure.…”
Section: Anionic Homo Phospho-fries Rearrangementmentioning
confidence: 99%
“…Redox‐active ferrocenyl‐functionalized five‐ and six‐membered heterocycles as well as aromatic and polyaromatic hydrocarbons are well suited as model compounds for studying intramolecular electron transfer processes, as they possess short electron transfer distances. They are easy to functionalize at the heterocyclic or aromatic hydrocarbon core and/or the redox‐active moiety, enabling the straightforward modification of the electronic properties.…”
Section: Introductionmentioning
confidence: 99%
“…DFT calculations showed that 5b non-covalently interacts with the single-walled carbon nanotube (SWCNT) sidewalls as provenb y, fore xample, disentangling experiments. In addition, CV studies of the as-obtained dispersions confirmed exohedralattachment of 5b at the SWCNTs.Redox-active ferrocenyl-functionalized five- [1] and six-membered [2] heterocyclesa sw ell as aromatic [2][3][4][5] and polyaromatic hydrocarbons [6][7][8][9] are well suited as model compounds for studying intramolecular electron transfer processes,a st hey possess short electron transfer distances. They are easy to functionalize at the heterocyclic or aromatic hydrocarbon core and/or the redox-active moiety,e nabling the straightforward modification of the electronic properties.…”
mentioning
confidence: 99%
“…In organophosphorus chemistry, rearrangements are less developed transformations, however, some examples can be found in the literature (Scheme 1). These include the famous Arbuzov rearrangement [29][30][31][32] as well as phospha-Fries ( [1,3]-rearrangements) [33][34][35][36][37], phospha-Brook ( [1,2]-rearrangement) [38][39][40][41][42], and [2,3]-sigmatropic rearrangements of propargyl and allylphosphinites [43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%